The effect of topical lidocaine on muscle artefacts in awake canine electroencephalogram recordings. (July 2016) - Ward, Jordan; James, Fiona; Monteith, Gabrielle
Highlights: Muscle artefacts are problematic in canine awake electroencephalography (EEG). Topical liposomal lidocaine was investigated to reduce EEG muscle artefact. No effect was found comparing lidocaine treatment to historical controls. Topical liposomal lidocaine does not reduce muscle artefacts in canine awake EEG. Abstract: Muscle artefacts in electroencephalogram recording data interfere with diagnostic accuracy. Lidocaine may reduce these artefacts. The objective of this study was to determine the effect of topical lidocaine on muscle artefacts in unanesthetized canine electroencephalogram (EEG) recording data. Topical 4% lidocaine was applied to each electrode site for six treated dogs prior to subdermal wire electrode placement and compared against historical untreated controls. Twenty-minute recordings began 30 min after lidocaine application. Three epochs (early, middle, and end) were sampled from each recording and scored for muscle artefact incidence and severity by two blinded reviewers. No significant treatment effects on incidence and severity were found. Application of topical lidocaine does not appear to reduce the occurrence of muscle artefacts in canine EEG recordings.